2017
DOI: 10.5194/cp-13-1063-2017
|View full text |Cite
|
Sign up to set email alerts
|

Centennial to millennial climate variability in the far northwestern Pacific (off Kamchatka) and its linkage to the East Asian monsoon and North Atlantic from the Last Glacial Maximum to the early Holocene

Abstract: Abstract. High-resolution reconstructions based on productivity proxies and magnetic properties of core LV63-41-2 (off Kamchatka) reveal prevailing centennial productivity/climate variability in the northwestern (NW) Pacific from the Last Glacial Maximum (LGM) to the early Holocene (EH). The age model of the core is established by AMS 14 C dating and by projections of AMS 14 C data of the nearby core SO-201-12KL through correlation of the productivity proxies and relative paleomagnetic intensity. The resulting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…According to our SST compilation (Figure 3), most SST records in the subarctic Pacific show abrupt warming into the BA and cooling into the YD. In detail, the BA warming was consistent with elevated primary productivity and reduced spring sea-ice coverage in the Northwestern Pacific (Caissie et al, 2010;Gorbarenko et al, 2017;Max et al, 2012;Méheust et al, 2016Méheust et al, , 2018 and Northeastern Pacific (Davies et al, 2011;Méheust et al, 2018). During the YD, the rapid cooling in the Northwestern Pacific and its marginal seas was closely coupled to extended spring sea-ice coverage (Max et al, 2012;Méheust et al, 2016Méheust et al, , 2018.…”
Section: Sst Changes In the Subarctic Pacific Since The Last Ice Agementioning
confidence: 68%
See 2 more Smart Citations
“…According to our SST compilation (Figure 3), most SST records in the subarctic Pacific show abrupt warming into the BA and cooling into the YD. In detail, the BA warming was consistent with elevated primary productivity and reduced spring sea-ice coverage in the Northwestern Pacific (Caissie et al, 2010;Gorbarenko et al, 2017;Max et al, 2012;Méheust et al, 2016Méheust et al, , 2018 and Northeastern Pacific (Davies et al, 2011;Méheust et al, 2018). During the YD, the rapid cooling in the Northwestern Pacific and its marginal seas was closely coupled to extended spring sea-ice coverage (Max et al, 2012;Méheust et al, 2016Méheust et al, , 2018.…”
Section: Sst Changes In the Subarctic Pacific Since The Last Ice Agementioning
confidence: 68%
“…We will explore the possible mechanisms responsible for these contrasting phase relationships in Section 4.2. Despite inconsistent patterns in the subarctic Pacific, the SST remained at relatively low values during HS1 on both sides of the subarctic Pacific (Figure 3), corresponding to the southward expansion of the spring sea‐ice coverage and low marine productivity (Davies et al., 2011; Gorbarenko et al., 2017; Max et al., 2012; Méheust et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third and last hypothesis is that a change(s) among the terrigenous deposits explain the lower SD ferromagnetic grains input into the central Okhotsk Sea. Previous studies reported contemporaneous (i.e., <500 ka) environmental changes during interglacial intervals such as decreasing of IRD (e.g., Nürnberg and Tiedemann, 2004;Gorbarenko et al, 2017) and the increasing of sea level (e.g., Thomas et al, 2009). The latter strongly modified the input of terrigenous sediments in the center of Okhotsk Sea (e.g., Liu et al, 2006;Nürnberg et al, 2011;Jimenez-Espejo et al, 2018).…”
Section: Paleoenvironment In the Central Okhotsk Sea During Stronger-interglacial/ Interglacial Intervalsmentioning
confidence: 99%
“…All these background conditions differ significantly from present background conditions. Previous studies suggest that, during the last deglaciation, a tight coupling between the Asian summer monsoon and the North Atlantic temperature changes exists at centennial to millennial timescales [13,[16][17][18]. However, the characteristics of multidecadal-scale oscillations of the vegetation and climate in the Asian monsoon region, and their linkages with the North Atlantic climates remain controversial.…”
Section: Introductionmentioning
confidence: 99%